2003
DOI: 10.1249/01.mss.0000098993.51693.0b
|View full text |Cite
|
Sign up to set email alerts
|

ACE I/D Polymorphism and Cardiac Adaptations in Adolescent Athletes

Abstract: The results of the study show that significant changes occur in cardiac morphology and function in adolescent athletes. Interestingly, the ACE I/D polymorphism was associated with the degree of cardiac hypertrophy but not with the occurrence of LVH itself.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Therefore individuals with athlete's heart could exhibit further cardiac adaptation in response to both different training and kind of practiced sport [22,23]. Although these modifications have been largely studied in elite athletes, very little informations are currently available about young elite athletes who share the same training load.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore individuals with athlete's heart could exhibit further cardiac adaptation in response to both different training and kind of practiced sport [22,23]. Although these modifications have been largely studied in elite athletes, very little informations are currently available about young elite athletes who share the same training load.…”
Section: Resultsmentioning
confidence: 99%
“…There is also evidence that angiotensin II is involved in cell growth (Weber, 1997) and that the D allele is associated with ventricular hypertrophy (Schunkert et al 1994). Accordingly, several studies reported an association between the D allele and left ventricular mass of athletes (Fatini et al 2000; Nagashima et al 2000; Hernandez et al 2003; Rizzo et al 2003). Finally, Ashley et al (2006) recently reported that in ultramarathon runners, homozygotes for the D allele exhibited an increase in sympathovagal balance, resulting in greater sympathetic activation after the race that may have served to limit the decline in left ventricular function.…”
Section: Discussionmentioning
confidence: 99%
“…The association between ACE genotype and left ventricular growth in response to exercise, both in diseased patients and in elite athletes, is slightly better established (van Berlo and Pinto 2003). Significant associations between the D allele of ACE and LVM have been reported in several studies of athletes (Fatini et al 2000;Herna´ndez et al 2003;Nagashima et al 2000;Rizzo et al 2003) and individuals exposed to physical training (Montgomery et al 1997), although, in other athlete cohorts, the association between the ACE D allele and LVM was only significant in combination with other genetic variants (Diet et al 2001) or was not identified at all (Karjalainen et al 1999). The association does not appear to be present in untrained healthy controls (Kauma et al 1998;Linhart et al 2000) suggesting that any influence of ACE genotype on cardiac function involves an interaction between genotype and training.…”
Section: Genetic Associations With Performance-related Traitsmentioning
confidence: 94%